Comparison of three synthetic unit hydrograph methods - Kiu, Kwong Lieng (Universiti Malaysia Sarawak, (UNIMAS), 2000)
One of the most important engineering considerations in hydraulic structures design is the potential flood level in the relevant water delivery channel. In order to estimate the potential flood level, the relevant watershed rainfall-runoff and hydrological characteristics relationship have to be well known. This requires well- distributed rain gages and discharge stations over the watershed. However, this is what we are lacking in Sarawak. To overcome the problem above, several Synthetic Unit Hydrograph Methods have been developed over years ago. Generally, the synthetic unit hydrograph methods are used for synthesizing the unit hydrograph for ungaged catchment based on the catchment hydrological characteristics. Each method provides respective empirical equations for deriving the unit hydrograph. However, these empirical equations are only applicable to specific regions for which they are derived, or at least they should be applied to the watersheds having similar hydrological characteristics. The main point of this project is to study several Synthetic Unit Hydrograph Methods and comparing among them to find out which method is most applicable to the peat soil watersheds. The selected Synthetic Hydrograph Method will be used for estimating the outflow hydrograph for the remote watersheds, which are lacking of measured stream flow data or ungaged catchment